METODE PEMBIASAAN SEBAGAI UPAYA DALAM PENANAMAN KEDISIPLINAN ANAK TERHADAP PELAKSANAAN IBADAH (TELA’AH HADITS NABI TENTANG PERINTAH MENGAJARKAN ANAK DALAM MENJALANKAN SHOLAT) - Imas Jihan Syah (JCE (Journal of Childhood Education), 2018)
Various methods used by parents or teachers as educators as an effortto implement a plan that has been prepared to achieve learning objectives for students in both real and practical activities. These include habituation methods. Basically every method has advantages and disadvantages. For that educator must be able to choose the method with various considerations. Method of habituation is a method that takes place by familiarizing the students to think, behave and say and do all the activities that have been determined to create positive habits in the life of the students. For that, this method takes a relatively long time. Prayer is a pillar of religion. It requires habituation in implementing it since the age of tamyiz, as the Prophet said. Habituation also functions in instilling discipline of children. It should be noted, however, that in instilling these habits the educator should pay attention: the principle of preserving the fitrah of the child, strived to develop the potential of the child, is directed and done gradually.